1972
DOI: 10.1161/01.cir.45.4.815
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Middle-Aged Men Developing Coronary Heart Disease in Five Years

Abstract: Characteristics of 11,132 men aged 40-59 years and free from coronary heart disease (CHD) at entry were related to follow-up experience, using multivariate analysis. In 5 years among 2,404 U. S. railroad men and 8,728 European men there were 615 cases of CHD, 214 of whom died from CHD or suffered definite nonfatal infarction. With five entry characteristics (age, systolic blood pressure, serum cholesterol, smoking habit, and body mass index), multiple logistic solutions for Europeans and Americans, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
6

Year Published

1972
1972
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(70 citation statements)
references
References 13 publications
2
61
1
6
Order By: Relevance
“…The Mediterranean diet, characterized by a high consumption of monounsaturated fatty acids (MUFA), has been proposed as a healthy dietary standard because it is associated with a low rate of cardiovascular mortality [6]. However, we have demonstrated that not all MUFA-rich oils exert the same effects on the magnitude and duration of postprandial triglyceridemia [7].…”
Section: Introductionmentioning
confidence: 88%
“…The Mediterranean diet, characterized by a high consumption of monounsaturated fatty acids (MUFA), has been proposed as a healthy dietary standard because it is associated with a low rate of cardiovascular mortality [6]. However, we have demonstrated that not all MUFA-rich oils exert the same effects on the magnitude and duration of postprandial triglyceridemia [7].…”
Section: Introductionmentioning
confidence: 88%
“…In 1974, the composite risk score for coronary artery disease (CAD) was calculated according to the contemporary Keys' risk equation. 20 It takes into account age, systolic blood pressure, cholesterol, smoking and BMI, and gives the 5-year risk (%) of CAD among European men aged 40-59 years. The risk could not be assessed according to the Framingham equation because serum high-density lipoprotein cholesterol was not available.…”
Section: Baseline Risk Factorsmentioning
confidence: 99%
“…In 1974 the men were also asked questions on how they rated their present health and physical fitness on a 5-step scale ("very good", "good", "fair", "poor", "very poor"). To reflect composite risk of coronary artery disease, the Keys' risk score [6] including age, BMI, smoking, cholesterol and systolic blood pressure was calculated in 1974.…”
Section: Baseline Examinations In 1974 and Questionnaire Surveys In 1mentioning
confidence: 99%